1993
DOI: 10.1192/bjp.162.1.118
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical Memory in Depression: State or Trait Marker?

Abstract: Two cognitive measures were used to assess 22 patients who met DSM-III-R criteria for major depressive disorder: the Autobiographical Memory (AM) test and the Dysfunctional Attitude Scale. They were followed up over seven months. Measurement of dysfunctional attitudes did not predict outcome at seven months. Overgeneral recall on the AM test at initial assessment, especially for emotionally positive memories, was highly correlated with failure to recover from depression and accounted for 33% of the variance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
374
11
11

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 405 publications
(426 citation statements)
references
References 13 publications
30
374
11
11
Order By: Relevance
“…The data replicate earlier reports that a higher level of memory specificity at admission predicts less depression at 7-month follow-up, even when initial depression levels were partialed (Brittlebank et al, 1993;Dalgleish et al, 2001;Peeters et al, 2002). In the present study, it was specificity to negative cues that was related to depression outcome, replicating Peeters et al (2002).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The data replicate earlier reports that a higher level of memory specificity at admission predicts less depression at 7-month follow-up, even when initial depression levels were partialed (Brittlebank et al, 1993;Dalgleish et al, 2001;Peeters et al, 2002). In the present study, it was specificity to negative cues that was related to depression outcome, replicating Peeters et al (2002).…”
Section: Discussionsupporting
confidence: 90%
“…About 29% of the first responses were OGMs, which is comparable to Brewin et al (1999), but lower than the percentage reported by Brittlebank et al (1993;54%). Information on the stability of scores is provided in Table 2.…”
Section: Amt Performance and Its Stabilitycontrasting
confidence: 52%
See 1 more Smart Citation
“…Brittlebank and colleagues found that OGM in a sample of 22 depressed patients predicted the persistence of depression at 7-month follow-up (Brittlebank, Scott, Williams, & Ferrier, 1993). Similar findings were obtained by Peeters et al (2002) and by Raes et al (2006).…”
Section: Overgeneral Autobiographical Memorysupporting
confidence: 53%
“…The same number of cues was used in a previous study of people with persecutory delusions (Kaney et al, 1999), and a higher number of words increases the probability that parametric analyses may be used. Cue words for the present study were selected from a pool used by Brittlebank et al (1993), with the four sets of six words approximately matched according to emotionality ratings and Kucera-Francis frequency (Kucera & Francis, 1967). Negative and positive words were alternated with negative first, in order to end the procedure with a positive memory.…”
Section: Verbal Cognitive Tasksmentioning
confidence: 99%